Synergistic Effect of Conditioned Medium from Amniotic Membrane Mesenchymal Stromal Cells Combined with Paclitaxel on Ovarian Cancer Cell Viability and Migration in 2D and 3D In Vitro Models - Paola Chiodelli; Patrizia Bonassi Signoroni; Elisa Scalvini; Serafina Farigu; Elisabetta Giuzzi; Alice Paini; Andrea Papait; Francesca Romana Stefani; Antonietta Rosa Silini; Ornella Parolini (Pharmaceutics)
Background: Ovarian cancer accounts for more deaths than any other cancer of the female reproductive system. Despite standard care, recurrence due to tumor spread and chemoresistance is common, highlighting the need for novel therapies. Mesenchymal stromal cells from the human amniotic membrane (hAMSC) and the intact amniotic membrane (hAM) are promising due to their secretion of tumor-modulating bioactive factors, accessibility from biological waste, and ethical favorability. Furthermore, unlike isolated cells, hAM provides an easier, clinically translatable product. We previously demonstrated that hAMSC can inhibit tumor cell proliferation, both in contact and transwell settings, suggesting that hAMSC secrete bioactive factors able to target tumor cells. This study evaluates the anti-tumor effects of bioactive factors from hAMSC and hAM conditioned medium (CM) on ovarian cancer cells in 2D and 3D models, alone or with paclitaxel. Methods: The impact of CM, alone or with paclitaxel, was tested on ovarian cancer cell proliferation, migration, invasion, and on angiogenesis. Results: hAMSC-CM and hAM-CM inhibited the proliferation and migration in 2D cultures and reduced spheroid growth and invasion in 3D models. Combining CM with paclitaxel enhanced anti-tumor effects in both settings. Conclusions: hAMSC-CM and hAM-CM show therapeutic potential against ovarian cancer, with synergistic benefits when combined with paclitaxel.